2022
DOI: 10.3389/fmats.2022.871003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for the Growth of Two-Dimensional Layered InSe Thin Films on Amorphous Substrate by Molecular Beam Epitaxy

Abstract: A two-dimensional (2D) material known as indium selenide (InSe) is widely considered a promising layered semiconductor with potential applications in electronics and optoelectronics. However, the single phase of InSe is still a challenge due to the close formation energy of InSe and In2Se3. In this study, we demonstrate a novel growth method for 2D InSe with an indium precursor layer by molecular beam epitaxy. Indium pre-deposited on substrate at room temperature followed by growth of InSe at 550°C can overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…According to the theoretical calculation results, the as-deposited indium selenide thin film will be Se-rich and In-poor even sputtered from the 1:1 InSe target, which is consistent with the EDS characterization data. Based on the experimental results and previous literature [27], it seems that the priority formation of the In 2 Se 3 phase takes place when the as-deposited film is In-deficient. Consequently, we developed a co-deposition scheme using both an InSe and In target to ensure that the indium is stable and sufficient during the growth of indium selenide thin films.…”
Section: Difficulties and Challengesmentioning
confidence: 53%
“…According to the theoretical calculation results, the as-deposited indium selenide thin film will be Se-rich and In-poor even sputtered from the 1:1 InSe target, which is consistent with the EDS characterization data. Based on the experimental results and previous literature [27], it seems that the priority formation of the In 2 Se 3 phase takes place when the as-deposited film is In-deficient. Consequently, we developed a co-deposition scheme using both an InSe and In target to ensure that the indium is stable and sufficient during the growth of indium selenide thin films.…”
Section: Difficulties and Challengesmentioning
confidence: 53%
“…They observed that monolayer InSe exhibits a highly conductive 2D electron gas due to the substrate doping effect, which is a promising characteristic for fabricating FET with high carrier mobility. In 2022, Hsiao et al [76] pre-deposited the Indium on the substrate at room temperature and grew a pure 22 nm γ-InSe film at 550 • C. This method can suppress the In 2 Se 3 phase and allows for a wider choice of substrates. Until now, large-area 2D InSe flakes with thickness uniformity can be prepared, which paves the way to investigate its carrier and thermal transport.…”
Section: The Down-top Methodsmentioning
confidence: 99%
“…Although the exfoliation methods have been widely used to investigate 2D III-VI semiconductors’ exceptional electrical properties, synthesizing large-area high-quality layered materials still requires bottom-up strategies, which are more suitable to be realized for industrial applications. To date, epitaxial growth by chemical vapor deposition (CVD), pulsed laser deposition (PLD), or molecular beam epitaxy (MBE) has been used for the synthesis of 2D III-VI metal chalcogenides [ 10 , 11 , 12 , 13 , 14 , 15 ]. However, the synthesis of single-phase indium selenide is still a challenge by chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%